2008
DOI: 10.1007/s11095-008-9766-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Method for Formulating Stable siRNA-Loaded Lipid Particles for In vivo Use

Abstract: This paper describes a simple method of formulating PEGylated siRNA-loaded lipid particles. Given the ease of preparation, long term stability and favourable characteristics for in vivo delivery, our work represents an advance in lipid formulation of siRNA for in vivo use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 40 publications
4
115
1
Order By: Relevance
“…administration. 7 In addition to the simplicity of the preparation procedure, we also showed that these freeze-dried, lipidbased, formulations are highly stable even after storage at room temperatures for 1 month.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…administration. 7 In addition to the simplicity of the preparation procedure, we also showed that these freeze-dried, lipidbased, formulations are highly stable even after storage at room temperatures for 1 month.…”
Section: Introductionmentioning
confidence: 73%
“…We, therefore, subsequently evaluated the feasibility of delivering siRNA to solid cervical cancer tumours using our previously reported HFDM-formulated PEGylated lipidic system. 7 Serum stability and pharamacokinetic profiles of HFDM-formulated nucleic acid-loaded lipid particles We have previously established the ability of HFDM-formulated lipid particles to accumulate in subcutaneous tumours after systemic administration. 7 Here, we aimed to characterize these particles further via assessing their serum stability as well as their pharmacokinetic profile.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, nanoparticles can be prepared without an extrusion step under conditions where the lipid concentrations fall below their solubilities in the mixed solvents, leading to formation of liposomes with particle diameter <200 nm without any needs of extrusion [43]. In addition, some investigators have reported preparation of siRNA-loaded liposomes by using a freeze-dry procedure [45], although this procedure may result in unintended structural alterations [46]. Moreover, to package siRNA, some groups utilized significantly more complex liposome formulations.…”
Section: Introductionmentioning
confidence: 99%